Effects of magnesium supplementation on improving hyperglycemia, hypercholesterolemia, and hypertension in type 2 diabetes: A pooled analysis of 24 randomized controlled trials - Xu, Lianbin; Li, Xiuli; Wang, Xinhui; Xu, Mingqing (Frontiers in Nutrition, 2023)
Background: Although several studies presented that low magnesium status is associated with diabetes, the effects of magnesium intervation on improving clinical outcomes of type 2 diabetes have yielded conflicting results. Methods: PubMed, ScienceDirect, and Web of Science databases were searched for peer-reviewed literatures published by April 30, 2022 to evaluate the effects of magnesium supplementation on glycemic, circulating lipids, and blood pressure control in type 2 diabetes, and to explore the associated practical details. Results: 24 randomized controlled trials involving 1,325 type 2 diabetes revealed that subjects who received magnesium supplementation had statistically significant reductions in fasting blood sugar (FBS), glycosylated hemoglobin A1c (HbA1c), systolic blood pressure (SBP) and diastolic blood pressure (DBP), with WMD values of -0.20 mM (95% CI: -0.30, -0.09), -0.22 % (95% CI: -0.41, -0.03), -7.69 mmHg (95% CI: -11.71, -3.66) and -2.71 mmHg (95% CI: -4.02, -1.40), respectively. Detailed subgroup analyses demonstrated that health status of participants including age, body mass index (BMI), country, duration of diease, baseline magnesium level and baseline glycaemic control condition as well as magnesium formulation, dosage and duration of intervention influenced the effects of magnesium addition. Dose-effect relationships showed that 279 mg/d for 116 d, 429 mg/d for 88 d and 300 mg/d for 120 d are the average optimal dosages and durations for improving glycemic, circulating lipids, and blood pressure controls, respectively. Conclusions: These results provide clinically relevant information on the adjuvant therapy of magnesium for improving hyperglycemia, hypercholesterolemia, and hypertension in type 2 diabetes.